2019
DOI: 10.3390/ijms20174274
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Functionality of Cytochrome P450 4 (CYP4) Genetic Polymorphisms and Their Clinical Implications

Abstract: Enzymes in the cytochrome P450 4 (CYP4) family are involved in the metabolism of fatty acids, xenobiotics, therapeutic drugs, and signaling molecules, including eicosanoids, leukotrienes, and prostanoids. As CYP4 enzymes play a role in the maintenance of fatty acids and fatty-acid-derived bioactive molecules within a normal range, they have been implicated in various biological functions, including inflammation, skin barrier, eye function, cardiovascular health, and cancer. Numerous studies have indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 158 publications
2
39
0
2
Order By: Relevance
“…In addition, we found no inhibitory effect from the other CYP4F substrates at low concentrations except for PGA 1 , which is one of the classical substrates of CYP4F enzymes, since other CYP4F-substrates could also be catalyzed by other CYP family enzymes besides CYP4F. Taken together, these findings led us to select CYP4F isoforms as α-ESA saturase, consistent with previous reports showing that CYP4As metabolize intermediatechain fatty acids fatty acids with C10 to 16 carbon chain 29 , while CYP4Fs catalyze long-chain fatty acids C16 to 26 53 . However, we could not determine the specific CYP4F enzyme involved due to a lack of a selective marker substrate for the activity of individual CYP4F enzymes in the study of the effect of CYP-substrates on CLA formation, although PGA 1 could be used as a nonselective marker substrate for CYP4F enzymes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, we found no inhibitory effect from the other CYP4F substrates at low concentrations except for PGA 1 , which is one of the classical substrates of CYP4F enzymes, since other CYP4F-substrates could also be catalyzed by other CYP family enzymes besides CYP4F. Taken together, these findings led us to select CYP4F isoforms as α-ESA saturase, consistent with previous reports showing that CYP4As metabolize intermediatechain fatty acids fatty acids with C10 to 16 carbon chain 29 , while CYP4Fs catalyze long-chain fatty acids C16 to 26 53 . However, we could not determine the specific CYP4F enzyme involved due to a lack of a selective marker substrate for the activity of individual CYP4F enzymes in the study of the effect of CYP-substrates on CLA formation, although PGA 1 could be used as a nonselective marker substrate for CYP4F enzymes.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that the inhibitors of CYP 1 38 , 2 39,40 , and 3 41 family enzymes had minimal or modest inhibitory activities. However, CYP1-3 contain major xenobiotic-metabolizing enzymes responsible for the metabolism of the majority of drugs and other xenobiotics 42,43 , while CYP4 enzymes typically metabolize fatty acids 29,44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dataset, from a separate study, consisted of hepatic RNAseq analysis performed on control fetal female and male livers at a slightly later gestation (gestational D90). Expression of hepatic progesterone metabolising enzymes CYP3A4 , CYP2C9 , CYP2C19 21 , 22 and xenobiotic metabolising enzymes CYP2C18, CYP2J2 and CYP4F11 23 , 24 were decreased in fetal males as compared with fetal females (Fig. 2 a–f; P < 0.05–0.001).…”
Section: Resultsmentioning
confidence: 93%
“…For the third gene in (Table 1), PAX8, differential DNA methylation was identified to associate with gestational famine exposure and metabolic traits [28]. Other interesting genes linked to top probes of ( Table 1) include PPP1R3A whose SNP variation has been associated with risk of type 2 diabetes and CYP4F12 which belongs to the cytochrome P450 4 (CYP4) family implicated in various biological functions including inflammation, cardiovascular health, and cancer [29,30].…”
Section: Discussionmentioning
confidence: 99%